The clinical and financial implications of a decade of prostate biopsies in the NHS: analysis of Hospital Episode Statistics data 2008–2019. (22nd April 2020) - Tamhankar, Ashwin Sunil; El‐Taji, Omar; Vasdev, Nikhil; Foley, Charlotte; Popert, Rick; Adshead, Jim
Abstract : Objective: To evaluate the clinical and financial implications of a decade of prostate biopsies performed in the UK National Health Service (NHS) through the transrectal (TR) vs the transperineal (TP) route. Methods: We conducted an evaluation of the TR vs the TP biopsy approach in the context of 28 days post‐procedure complications and readmissions. A secondary evaluation of burden of expenditure in NHS hospitals over the entire decade (2008–2019) was conducted through examination of national Hospital Episode Statistics (HES) data. Results: In this dataset of 486 467 prostate biopsies (387 879 TR and 98 588 TP biopsies), rates of infection and sepsis were higher for the TR compared to the TP cohort (0.53% vs 0.31%; P < 0.001, confidence interval 99% ). Rates of sepsis have more than doubled for TR biopsies in the last 2 years compared to the previous decade (1.12% vs 0.53%). Infective complications were the main reasons for readmissions in the TR cohort, whereas urinary retention was the predominant reason for readmission in the TP cohort. Over the last decade, non‐elective (NEL) readmissions seem higher for the TP group; however, in the last 2 years these have reduced compared to the TR group (3.54% vs 3.74%). The cost estimates for NEL readmissions for the entire decade were £33, 589, 527.00 and £7, 179, 926.00 respectively, for TR and TP cohorts ( P < 0.001). Estimated costs per patient readmission were £2, 225.00 and £1, 758.00 in the TR and TP groups ( P < 0.001). Conclusions: Evaluation of nearly half a million prostate biopsies in the NHS over the entire decade gives sufficient evidence for the distinct advantages of the TP route over the TR route in terms of reduced infections and burden of expenditure. In addition, there is a potential for savings both in upstream and downstream costs if biopsy is performed under a local anaesthetic.